Sulindac inhibits pancreatic carcinogenesis in LSL-Kras(G12D)-LSL-Trp53(R172H)-Pdx-1-Cre mice via suppressing aldo-keto reductase family 1B10 (AKR1B10) - Li, Haonan (Oxford University Press, 2013)
Sulindac has been identified as a competitive inhibitor of aldo-keto reductase 1B10 (AKR1B10), an enzyme that plays a key role in carcinogenesis. AKR1B10 is overexpressed in pancreatic ductal adenocarcinoma (PDAC) and exhibits lipid substrate specificity, especially for farnesyl and geranylgeranyl. There have been no studies though showing that the inhibition of PDAC by sulindac is via inhibition of AKR1B10, particularly the metabolism of farnesyl/geranylgeranyl and Kras protein prenylation. To determine the chemopreventive effects of sulindac on pancreatic carcinogenesis, 5-week-old LSL-Kras(G12D)-LSL-Trp53(R172H)-Pdx-1-Cre mice (Pan(kras/p53) mice) were fed an AIN93M diet with or without 200 p.p.m. sulindac (n = 20/group). Kaplan–Meier survival analysis showed that average animal survival in Pan(kras/p53) mice was 143.7±8.8 days, and average survival with sulindac was increased to 168.0±8.8 days (P < 0.005). Histopathological analyses revealed that 90% of mice developed PDAC, 10% with metastasis to the liver and lymph nodes. With sulindac, the incidence of PDAC was reduced to 56% (P < 0.01) and only one mouse had lymph node metastasis. Immunochemical analysis showed that sulindac significantly decreased Ki-67-labeled cell proliferation and markedly reduced the expression of phosphorylated extracellular signal-regulated kinases 1 and 2 (ERK1/2), c-Raf and mitogen-activated protein kinase kinase 1 and 2. In in vitro experiments with PDAC cells from Pan(kras/p53) mice, sulindac exhibited dose-dependent inhibition of AKR1B10 activity. By silencing AKR1B10 expression through small interfering RNA or by sulindac treatment, these in vitro models showed a reduction in Kras and human DNA-J homolog 2 protein prenylation, and downregulation of phosphorylated C-raf, ERK1/2 and MEK1/2 expression. Our results demonstrate that sulindac inhibits pancreatic carcinogenesis by the inhibition of Kras protein prenylation by targeting AKR1B10.